2019
DOI: 10.1017/s002221511900210x
|View full text |Cite
|
Sign up to set email alerts
|

Supra-auricular and post-auricular resection of pre-auricular and post-auricular sinuses

Abstract: ObjectiveThis study aimed to classify the pre-auricular sinus before performing radical dissection, so as to achieve optimal aesthetic results.MethodsThe recent five-year clinical data of 53 patients with a congenital pre-auricular sinus and infection treated in the hospital were reviewed. According to the sinus course, pre-auricular and post-auricular types were defined, and regional dissection was performed using the modified supra-auricular or post-auricular approach.ResultsAll patients achieved primary int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…4 Ding et al reported on the pits of two ears (2/53, or 3.8%) which were located in the crus of the helix, and 51 ears which had pits in the anterior portion of the helix. 9 In our study, variant preauricular sinuses accounted for 6.7% of all preauricular sinuses, a similar rate to that of Yeo et al…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…4 Ding et al reported on the pits of two ears (2/53, or 3.8%) which were located in the crus of the helix, and 51 ears which had pits in the anterior portion of the helix. 9 In our study, variant preauricular sinuses accounted for 6.7% of all preauricular sinuses, a similar rate to that of Yeo et al…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the fistula locations included the ascending helix crus (15 ears, most common), the infra‐auricular area (3 ears), the supra‐auricular area (1 ear), and anterior to tragus (1 ear) 4 . Ding et al reported on the pits of two ears (2/53, or 3.8%) which were located in the crus of the helix, and 51 ears which had pits in the anterior portion of the helix 9 . In our study, variant preauricular sinuses accounted for 6.7% of all preauricular sinuses, a similar rate to that of Yeo et al…”
Section: Discussionmentioning
confidence: 99%